Analisis Regresi Spasial dan Pola Penyebaran pada Kasus Demam Berdarah Dengue (DBD) - Hisbullah, Hisbullah; Al Jauziah, Hanief; Soraya, Siti; Azizah, Istin Fitriani (CORISINDO 2025, 2025)
Dengue Hemorrhagic Fever (DHF) is one of the endemic diseases whose spread is greatly influenced by environmental conditions, available health facilities, and the spatiality of an area. This study aims to analyze the pattern of DHF case distribution in NTB Province using the spatial regression method. By utilizing secondary data obtained from 2022, this study also analyzes the influence of five independent variables, namely population, number of general hospitals, poverty rate, number of health centers, and number of houses affected by flooding on the number of DHF cases in each district/city. Spatial analysis was carried out using the Spatial Autoregressive (SAR) model, preceded by a positive spatial autocorrelation test through the Moran index. The results of the study showed significant positive spatial autocorrelation (p <0.05), which indicates that areas with a high number of cases tend to border areas with high cases. The SAR model was proven to be better than the OLS model based on the R² (0.9986) and AIC (101.669) values. This finding is expected to be the basis for planning priority area interventions in controlling DHF cases in NTB Province in a spatial and targeted manner.